2014
DOI: 10.1094/pdis-07-13-0724-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Bacterial Leaf Blight of Carrot Caused by Xanthomonas hortorum pv. carotae in Korea

Abstract: In December 2012, symptoms of typical bacterial leaf blight were observed on carrot plants (Daucus carota L. subsp. sativus) cultivated in commercial fields in Kujwa, Jeju, Korea. The disease was detected in 40% of 50 fields surveyed with an incidence of 10% on average. The bacterial leaf blight lesions on leaf blades were elongated, dark brown to black with water-soaked edges and chlorotic halos. Lesions were also crescent-shaped to V-shaped on leaflets. Four bacterial isolates were recovered on trypticase so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…carotae is pathogenic on wild carrot (Daucus carota) and its cultivated subspecies (D. carota subsp. sativus) (Kendrick, 1934;Myung et al, 2014;Temple et al, 2013), while Russian dandelion (Taraxacum kok-saghyz) is the only reported host of X. hortorum pv.…”
Section: Hos T R Ang Ementioning
confidence: 99%
See 3 more Smart Citations
“…carotae is pathogenic on wild carrot (Daucus carota) and its cultivated subspecies (D. carota subsp. sativus) (Kendrick, 1934;Myung et al, 2014;Temple et al, 2013), while Russian dandelion (Taraxacum kok-saghyz) is the only reported host of X. hortorum pv.…”
Section: Hos T R Ang Ementioning
confidence: 99%
“…The presence of a chlorotic halo around spots or lesions is pathovar-or plant/cultivar-dependent. For example, a chlorotic halo is present around lesions caused by X. hortorum pvs pelargonii, hederae, and taraxaci, but its presence varies in angular leaf spot caused by X. hortorum pvs carotae, vitians, and gardneri (Daughtrey & Wick, 1995;Gilbertson, 2002;Myung et al, 2014;Nameth et al, 1999;Pruvost et al, 2010). In advanced infection stages, lesions and spots usually turn dark in colour (brown to black) on plant parts affected by X. hortorum pvs pelargonii, hederae, carotae, gardneri, and vitians.…”
Section: Dis E a S E Symp Tomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial blight is a common disease of carrot wherever carrot is cropped. The most recent reports concerned Mauritius, Indiana state in the USA, Korea and Spain (Pruvost et al, 2010;du Toit et al, 2014;Myung et al, 2014;Palomo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%